Stanisław Barańczak jako krytyk języka. Wokół dwóch esejów z tomu Poezja i duch Uogólnienia - Trubicka, Hanna (Wydawnictwo Naukowe UAM w Poznaniu, 2011)
The articles derives from a conviction that the later essays writing of Stanisław Barańczak in one of its important aspects is a criticism of the morally destructive features of the language. His theory of poetry as a particular kind of speech – directed to the concrete, multimeaning, always individual – is a simple consequence of a conviction abot what should be the language in general results from the deeply ethical objection to the generality, exaggerated abstractness, one-sidedness of an opinion. Manifestations of such “a laying the language in charge”, to use Barańczak’s own words, I can be found mostly in his two late essays titled Człowiek, Który Za Dużo Wie [The Man Who Knows Too Much] and Poezja i duch Uogólnienia [Poetry and the Spirit of Generalisation]. In their rhetoric I am looking for the supplement of his relation to language.
Stanisław Barańczak as a critic of language. On two essays from Poetry and Spirit of Generalisation